The category of node-and-choice forms for extensive-form games - Peter Alfred Streufert (The University of Western Ontario, Department of Economics, 2016)
It would be useful to have a category of extensive-form games whose isomorphisms specify equivalences between games. Toward this goal, Streufert (2016) introduced the category of node- and-choice preforms, where a "preform" is a rooted tree together with choices and information sets. This paper takes another step: It introduces the category of node-and-choice forms, where a "form" is a preform augmented with players. In addition, it derives some consequences of the category's morphisms and provides a characterization of the category's isomorphisms.
Keywords: C72; 330; preform; game form; isomorphism